Why does intermarriage increase immigrant employment? ; the role of networks - Delia Furtado; Nikolaos Theodoropoulos (Institute for the Study of Labor (IZA), 2010)
Social networks are commonly understood to play a large role in the labor market success of immigrants. Using 2000 U.S. Census data, this paper examines whether access to native networks, as measured by marriage to a native, increases the probability of immigrant employment. We start by confirming in both least squares and instrumental variables frameworks that marriage to a native indeed increases immigrant employment rates. Next, we show that the returns to marrying a native are not likely to arise solely from legal status acquired through marriage or characteristics of native spouses. We then present several pieces of evidence suggesting that networks obtained through marriage play an important part in explaining the relationship between marriage decisions and employment.
Keywords: J61; J12; J21; 330; immigration; marriage; employment; networks